Integrative Pain Management. - Thompson, Diana L. (Handspring Publishing Limited, 2016)
This book provides an overview of pain mechanisms as currently understood, and details a variety of approaches to pain management used across a wide range of complementary disciplines. A final chapter integrates these body-based and mind-body approaches, and helps the clinician offer the most effective care for the patient.